Influence of the Marble dust on Hardened properties of the Concrete - A State of art review - Manwani, M; Goyal, PK (International Journal of Computer Sciences and Engineering, 2025)
This paper presents the state- of -art review of the influence of the marble dust on hardened properties of the Concrete. The main purpose of this review paper is to find out the great potential for the use of waste marble dust in concrete production, so that the environment must protect with the effect of waste marble dust. In this review paper, the influence of the marble dust on the hardened properties of concrete mix will be discussed in two segments. The first segment will discuss the impact of concrete by changing the soil from the marble dust and second segment deals with changing the cement from the marble dust.